Grid based docking study of some 2-(4-methylsulfonyl phenyl) pyrimidine derivatives (designed after QSAR studies) with Cyclooxygenase - Satish Sarankar; A.K Pathak (International Journal of Antibiotics, 2024)
Molecular docking helps in studying drug/ligand or receptor/ protein interactions by identifying the suitable active sites in protein, obtaining the best geometry of ligand-receptor complex and calculating the energy of interaction for different ligands to design more effective ligands. In Grid based docking, after unique conformers of the ligand are generated, the receptor cavity of interest is chosen and a grid is generated around the cavity. Cavity points are found and the centre of mass of the ligand is moved to each cavity point. All rotations of ligand are scanned at each cavity point where ligand is placed. Efficiency and precision of docking rely upon scoring function. Scoring functions are based on force fields that are used to simulate the functions of proteins. With known 3D structure of receptor molecule or protein, the binding affinity of the protein ligand complex was calculated and it is termed as Dock Score. In our research work, to know the biding affinity of some 2-(4-methylsulfonylphenyl) pyrimidine derivatives (designed after QSAR studies) with Cyclooxygenase-2, the compounds were docked with three different receptors namely Cyclooxygenase-2 (Prostaglandin synthase-2), Uninhibited Mouse Cyclooxygenase-2 (Prostaglandin Synthase-2) and Membrane Protein Prostaglandin H2 Synthase-1) using VLifeMDS software. Among all compounds, three compounds having 2,2-dibromoethanamine, 2,2-diiodoethanamine and 2,2,2-triiodoethanamine substituted pyrimidine derivatives showed best docking score with all three COX-2 receptors. With Prostaglandin synthase-2 after successful completion of docking process, the minimum score obtained was -6.199069, -6.180829 and -6.049794 for three compounds respectively. The compounds were docked with a different receptor Uninhibited Mouse Cyclooxygenase-2 and the same three compounds showed minimum score of -6.293567, -6.202445, -6.100384 respectively. The docking score was found -6.345966, -6.245738, -6.150805 with Membrane Protein Prostaglandin H2 Synthase-1 with the same substituted pyrimidine derivatives. The present research work opened a new path to fulfill the increasing demand of COX-2 inhibitors which can be used in the treatment and cure of various ailments those are mediated through COX-2 pathway.
Keywords: Cyclooxygenase-2; Docking; Docking score; Pyrimidine derivatives; VLifeMDS software